ANALISA KETERAMPILAN KOLABORASI MAHASISWA MENGGUNAKAN ALUR MERDEKA MATA KULIAH FISIKA DASAR MATERI KAPASITOR - yolanda, yaspin (Al-Khazini, 2023)
This study aims to measure collaboration skills that appear in the realm of knowledge, skills and affective. Learning with independent flow approach, acronyms starting from self, concept exploration, collaboration space, guided reflection, contextual demonstration, understanding elaboration, connection between material, and real action. The research method using descriptive methods aims to answer or describe the state of collaboration skills of students of physics education at the PGRI Silampari university, Lubuklinggau city, which are taught in an independent flow. The object of research is 25 first semester students who are taking basic physics courses in the odd semester of the 2022/2023 period. The research instrument was in the form of a test in the realm of knowledge and non-test in the form of the domain of skills and attitudes. Instruments in the form of tests and non-diagnosis tests of collaboration skills. The descriptive data analysis technique aims to explain the data that has been obtained after collecting data on collaboration skills for all students. The results showed that the average achievement of collaboration skills in the realm of knowledge was 72.5% of students understood the concept and 27.5% had difficulty analyzing mathematical calculations in finding the measured quantity. The average achievement of student collaboration skills in the realm of skills is 45% of students are skilled as expected, 25% are skilled and 20% are starting to be skilled and 10% of students are not yet skilled. The average achievement of collaboration skills in the realm of attitude shows that 53.75% of students are developing as expected, 18.75% are developing and 27.5% are starting to develop.